A method to limit uncertainties in aerosol properties determined from comparative measurements. (January 2016) - Alonso, M.; Borra, J.P.
Abstract: Certain types of aerosol measurements require an experimental set up including two or more routes through which the particles are made to flow alternatively. Indeed, this appears to be critical to limit uncertainties in aerosol properties determined from comparative measurements. Typical examples are the comparison of the performance of different instruments and the measurement of particle filtration efficiency. Except for the presence of the test units (e.g. the instruments or devices to be compared) it is commonly accepted that the two routes must be identical: they should contain the same type and number of tubes, valves, junctions, bends, connectors, etc. For nanometer-sized particles undergoing substantial diffusion losses, the lack of perfect symmetry between the two routes induces discrepancies in measurements performed in both lines. This article provides a general methodology to avoid or reduce the errors arising from these possible asymmetries. The method consists in making two measurements, one with the given setup, the other with an alternative set up in which the test units have been exchanged. The correct result (e.g. filtration efficiency) is the geometric mean of the results obtained with the two alternative setups. The proposed methodology may seem tedious and time consuming, but doing so, the experimental measurement is not affected neither by possible errors due to a test aerosol changing with time nor by the possible asymmetry of the line accessories (valves, T׳s, connections, etc.).